Analisis Komparatif Tindak Pidana Pembunuhan Anak oleh Ibu Kandung Perspektif RKUHP dan Hukum Pidana Islam - Rina Gustiani (Rechtenstudent, 2021)
Children are an inseparable part of the lives of parents. A child is a gift from Allah SWT and is a young shoot of a successor to the nation's ideals. The existence of children has a strategic role in maintaining the continuity of the presence of the nation and state in the future. Therefore children need to get protection. However, it does not demand the possibility that children who should receive safety and love from their parents receive inappropriate treatment. Not a few in our country, the occurrence of parental violence against biological children such as hitting, beating with tools, throwing into the river, and even killing on the spot after he was born. So, in this case, there needs to be a study of criminal law, which will later be realized through positive criminal law (RKUHP) which will be present amid Indonesian legislation combined with Islamic criminal law that has been applied in areas with strong Islam previously such as Aceh. So that later, it can provide protection not only to the victim but to a perpetrator. This study uses a qualitative method through literature study with a comparative approach between the RKUHP and Islamic Criminal Law. There are differences between the RKUHP and Islamic Criminal Law. In the RKUHP, the mother's position as a parent is not a reason to then stop the criminal conviction. Meanwhile, in Islamic Criminal Law, the mother's position is essential because, according to Jumhur Ulama, a criminal sentence cannot be carried out when the suspect is a parent.